2020
DOI: 10.3390/ma13051131
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Implant–Abutment Connection on Clinical Outcomes and Microbial Colonization: A Narrative Review

Abstract: Introduction: Osseointegration are often suffering from oral conditions, especially, the micro gap at the implant–abutment connection represents a site for bacterial plaque aggregation, leading to increased inflammatory cells and causing peri-implantitis. Aim: The aim of this narrative review was to describe the different kinds of implant–abutment connections and their ability to reduce bacterial leakage and thus prevent peri-implantitis. Materials and methods: The following databases were consulted: Pubmed, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 25 publications
(31 reference statements)
0
51
0
Order By: Relevance
“…The implant surface structure and abutment interface may affect microbial colonization and disease progression (Belibasakis et al 2015; Lauritano et al 2020), whereas modification of its characteristics may enhance antimicrobial properties and clinical outcomes (Asensio et al 2019). The occurring biocorrosion of the implant surface can result in release of titanium particles and biological implant complications (Mombelli et al 2018).…”
Section: Implant Surface As a Modifier Of The Peri-implant Nichementioning
confidence: 99%
“…The implant surface structure and abutment interface may affect microbial colonization and disease progression (Belibasakis et al 2015; Lauritano et al 2020), whereas modification of its characteristics may enhance antimicrobial properties and clinical outcomes (Asensio et al 2019). The occurring biocorrosion of the implant surface can result in release of titanium particles and biological implant complications (Mombelli et al 2018).…”
Section: Implant Surface As a Modifier Of The Peri-implant Nichementioning
confidence: 99%
“…Furthermore, under load conditions, both microgaps can be widened further [ 19 ]. In this context, it could be demonstrated that the geometry of the implant–abutment connection can have an influence on the extent of microbial penetration and that implants with internal morse taper connection exhibit a lower contamination level compared to other geometries [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…It allows to create a coagulum chamber, described by Degidi et al, which is essential for the proper healing of the socket with the consequent reduction of bone resorption [ 50 ]. Furthermore, since the bacterial leakage in the implant-abutment interface is raised as the most important factor in the occurrence of inflammatory reactions around the implant [ 51 , 52 ], B.O.I.L protocol allows to not unscrew the healing abutment, before its final insertion, so as to prevent bacterial infiltration and the detachment of the hemidesmosomial junctions.…”
Section: Discussionmentioning
confidence: 99%